Clamouring for legal protection : what the great books teach us about people fleeing from persecution - Barsky, Robert F (London [England] : Hart Publishing, 2021)
"In this novel approach to law and literature, Robert Barsky delves into the canon of so-called Great Books, and discovers that many beloved characters therein encounter obstacles similar to those faced by contemporary refugees and undocumented persons. The struggles of Odysseus, Moses, Aeneas, Dante, Satan, Dracula and Alice in Wonderland, among many others, provide surprising insights into current discussions about those who have left untenable situations in their home countries in search of legal protection. Law students, lawyers, social scientists, literary scholars and general readers who are interested in learning about international refugee law and immigration regulations in home and host countries will find herein a plethora of details about border crossings, including those undertaken to flee pandemics, civil unrest, racism, intolerance, war, forced marriage, or limited opportunities in their home countries."--
Preface -- Introduction: Opening up the Great Books -- 1. Spreading Disease, or Inoculating Us from Intolerance? -- 2. Following Pathways, Networks and Guides -- 3. Opening Doors, and Scaling Walls -- 4. Confronting Inhospitable Spaces, and Hostile Hosts -- 5. Encounters with Aliens, Monsters and Terrorists -- Conclusion: From Persecution to Wonderland -- Bibliography -- Index.
Includes bibliographical references and index.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily.
Mode of access: World Wide Web.
Keywords: Refugees -- Legal status, laws, etc; Political refugees -- History; Refugees -- History; Persecution -- History; Immigration law; Electronic books